Measurement of attitudes in masculine organizational contexts - Monteiro, Rosa (2019)
Organizations developing equality plans must understand the persistence of workers’ asymmetric conceptions based on gender stereotype. This study was conducted in Portugal and aimed to identify whether there are more gender stereotypes in highly masculinized organizational contexts. A questionnaire “Men’s Polarized Gender Thinking Questionnaire (MPGQ)” was applied to a sample of 160 workers from two organizations: Águas Limpas and SOS. In the labor market, men with higher levels of education tend to present more equalitarian attitudes, while less educated men are less likely to recognize inequalities. Individuals’ schooling and education are crucial, as these aspects stand out as important vectors for the acquisition of a more equalitarian system of beliefs and social values on the theme of gender relations. The results show that the attitudes of men towards gender equality are not distributed randomly. These findings corroborate the warningsmade in research adopting intersectionality approaches.